Kista Bartholin: Laporan Kasus - Rahman, M. Rizki; Shariff, Fonda Octarianingsih (CV. Jasa Sukses Abadi, 2024)
Bartholin's cyst is a type of cystic tumor that is located in the vulva and is formed due to blockage of the Bartholin's gland duct. This blockage causes fluid buildup and cystic enlargement. A report noted that a 43 year old woman came to the Obstetrics and Gynecology Polyclinic at Pertamina Bintang Amin Hospital in Bandar Lampung, complaining of a lump in the genital area that had appeared since a year ago, the size of a quail egg, but the patient stated that she did not feel any pain. The treatment given includes antibiotics and analgesics, and it is recommended to undergo a surgical procedure using the marsupialization technique. Marsupialization is a procedure in which stabilization is carried out, that is, the cyst must be stabilized and gently retracted using finger pressure applied on both sides of the affected labium, below the cyst. Then an incision is made over the body of the cyst and within the hymeneal loop, usually at the 4-5 or 7-8 o'clock position from the introitus. The incision is generally made in a cross manner and extended up to 2-3 cm according to the size of the cyst.